Extended thrombotic prophylaxis in COVID-19 early discharge: A retrospective cohort study - Sebastiaan T. van’t Hoff; Gea Helfrich; Sanne Boerman; Hans A. Hardeman (PLoS ONE, 2026)
Introduction/Background Due to limits in available staff and space during the COVID-19 pandemic, home monitoring programmes were introduced, reducing strain on resources, and preventing readmissions. Several hospitals included prophylaxis for venous thrombotic events (VTE), as COVID-19 appeared to be thrombogenic. Other hospitals did not, expecting patients to be more mobile while at home. Our aim was to determine whether the administration of nadroparin has led to a difference in VTE occurrence between two groups of previously included patients. Materials and methods Retrospective cohort study of two cohorts included in home monitoring with the same protocol, except for nadroparin prophylaxis. Results 663 patients were analysed in equal groups from two hospitals. No significant difference was found in occurrence of VTE after discharge, readmissions in general or readmissions due to VTE in otherwise comparable groups. Discussion As opposed to trials determining thrombotic prophylaxis was of benefit after discharge due to COVID-19, we found no difference between our groups. Our study was retrospective and comprised data compiled over almost two years, which provides a relatively large sample size and overview through different treatment regimes. Conclusion For the future, thrombotic prophylaxis for COVID-19 home monitoring might not be indicated and reconsidered for different home monitoring programmes.